Corrigendum to ‘Quantification of the exposure of consumers and hairdressers to formaldehyde and oxalic acid after application of hair straightening products containing glyoxylic acid’ [Toxicol. Appl. Pharmacol. 515 (2026) 117940] - Nicola J. Hewitt; Carsten Goebel; Jens Diller; Anne Fuchs; Rolf Fautz; Brunhilde Blömeke; Katharina Schwarz; Shimpei Terasaka; Kazutoshi Saito; Rebecca Justiniano; Gábor von Bölcsházy (Toxicology and Applied Pharmacology, 2026)

Quantification of the exposure of consumers and hairdressers to formaldehyde and oxalic acid after application of hair straightening products containing glyoxylic acid - Nicola J. Hewitt; Carsten Goebel; Jens Diller; Anne Fuchs; Rolf Fautz; Brunhilde Blömeke; Katharina Schwarz; Shimpei Terasaka; Kazutoshi Saito; Rebecca Justiniano; Gábor von Bölcsházy (Toxicology and Applied Pharmacology, 2026)

Lessons from GPS-tagged Eurasian Curlews: synthesising movement ecology to inform conservation - Frédéric Jiguet; Aurélien Besnard; Pierrick Bocher; Andrea Kölzsch; Aleksi Lehikoinen; Markus Piha; Petr Procházka; Marie Donnez; Tuomas Seimola; Jimmy Allain; Lise Bartholus; Carole Doucerain; et al. (Biological Conservation, 2026)

Corrigendum to ‘Quantification of the exposure of consumers and hairdressers to formaldehyde and oxalic acid after application of hair straightening products containing glyoxylic acid’ [Toxicol. Appl. Pharmacol. 515 (2026) 117940] - Nicola J. Hewitt; Carsten Goebel; Jens Diller; Anne Fuchs; Rolf Fautz; Brunhilde Blömeke; Katharina Schwarz; Shimpei Terasaka; Kazutoshi Saito; Rebecca Justiniano; Gábor von Bölcsházy (Toxicology and Applied Pharmacology, 2026)

Suitability of the use of the intraperitoneal route in the in vivo micronucleus test to evaluate the genotoxicity of hair dyes - Nicola J. Hewitt; Hind Assaf Vandecasteele; Paul Benndorf; Rolf Fautz; Anne Fuchs; Karma Fussell; Carsten Goebel; Torben König; Fabrice Nesslany; Juliane Werner; Paul Fowler (Regulatory Toxicology and Pharmacology, 2026)

Plant metabolic responses to soil herbicide residues differ under herbivory in two woodland strawberry genotypes - Benjamin Fuchs; Marjo Helander; Kari Saikkonen; Petre I. Dobrev; Radomira Vankova; James D. Blande; Juha-Pekka Salminen; Niko Luntamo; Anne Muola (Science of The Total Environment, 2024)

Thermal and behavioural responses of moose to chemical immobilisation from a helicopter - Anne Randi Græsli; Alexandra Thiel; Larissa T. Beumer; Boris Fuchs; Fredrik Stenbacka; Wiebke Neumann; Navinder J. Singh; Göran Ericsson; Jon M. Arnemo; Alina L. Evans (European Journal of Wildlife Research, 2023)
Instrumentation and sample collection for wildlife research and management may require chemical immobilisation of animals, which may entail physiological and behavioural effects on them. It is therefore important to evaluate the immobilisation protocols to reduce the risk of mortality and morbidity of the handled animals and their populations. Using a multi-sensor approach, we assessed the short-term (< 10 days) thermal and behavioural responses of 10 adult female moose ( Alces alces ) equipped with ruminal temperature loggers and GPS collars with accelerometers to helicopter-based chemical immobilisations. We investigated the body temperature ( T b ), movement rates, and resting time before, during, and after recapture. Chemical immobilisations on average increased maximum T b by 0.71 °C during the capture day, and imposed longer travel distances during the capture day and the two following days (3.8 and 1.8 km, respectively), compared to a 10-day reference period before the immobilisation. The probability of resting was 5–6% lower on the capture day and the two following days compared to the reference period, and females with offspring had a higher probability of resting than females without. Maximum T b , movement rate, and resting time returned to pre-capture levels on an individual level 2 h, 3 days, and 3 days after the immobilisation, respectively. Chemical immobilisation of moose from a helicopter increases the energy expenditure deduced through movement and T b rise lasting for hours to days. Ecological and physiological studies aimed at inferring general patterns may encounter bias if including sensor and tracking data from tagged animals without accounting for potential post-capture effects.

Incorporating integrated testing strategy (ITSv1) defined approach into read-across (RAx) in predicting skin sensitization potency: ITSv1-based RAx - Kanako Nakayama; Anne Zifle; Sabrina Fritz; Anne Fuchs; Hitoshi Sakaguchi; Masaaki Miyazawa (Regulatory Toxicology and Pharmacology, 2023)

Lessons Learnt From Linking Global Recommendations With Localized Marine Restoration Schemes and Policy Options by Using Mixed Methods - Gesche Krause; Christine Wolf; Anne-Kathrin Happe; Jennifer Hauck; Pier Luigi Buttigieg; Nike Fuchs; Jan Scheve; Claudia König; Heidi Wittmer; Kristina Raab (Frontiers in Marine Science, 2020)

The AlpArray Seismic Network: A Large-Scale European Experiment to Image the Alpine Orogen - György Hetényi; Irene Molinari; John Clinton; Götz Bokelmann; István Bondár; Wayne C. Crawford; Jean-Xavier Dessa; Cécile Doubre; Wolfgang Friederich; Florian Fuchs; Domenico Giardini; Zoltán Gráczer; et al. (Surveys in Geophysics, 2018)

Metabolic versatility of a novel N 2 ‐fixing Alphaproteobacterium isolated from a marine oxygen minimum zone - Clara Martínez‐Pérez; Wiebke Mohr; Anne Schwedt; Julia Dürschlag; Cameron M. Callbeck; Harald Schunck; Julien Dekaezemacker; Caroline R. T. Buckner; Gaute Lavik; Bernhard M. Fuchs; Marcel M. M. Kuypers (Environmental Microbiology, 2018)
Summary The N 2 ‐fixing (diazotrophic) community in marine ecosystems is dominated by non‐cyanobacterial microorganisms. Yet, very little is known about their identity, function and ecological relevance due to a lack of cultured representatives. Here we report a novel heterotrophic diazotroph isolated from the oxygen minimum zone (OMZ) off Peru. The new species belongs to the genus Sagittula ( Rhodobacteraceae , Alphaproteobacteria ) and its capability to fix N 2 was confirmed in laboratory experiments. Genome sequencing revealed that it is a strict heterotroph with a high versatility in substrate utilization and energy acquisition mechanisms. Pathways for sulfide oxidation and nitrite reduction to nitrous oxide are encoded in the genome and might explain the presence throughout the Peruvian OMZ. The genome further indicates that this novel organism could be in direct interaction with other microbes or particles. NanoSIMS analyses were used to compare the metabolic potential of S. castanea with single‐cell activity in situ ; however, N 2 fixation by this diazotroph could not be detected at the isolation site. While the biogeochemical impact of S. castanea is yet to be resolved, its abundance and widespread distribution suggests that its potential to contribute to the marine N input could be significant at a larger geographical scale.

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

Das Wasserkraftpotenzial Österreichs im Spannungsfeld von Umweltpolitik und Klimawandel - Martin Fuchs; Ernst Zeller; Anne Joeppen; Herbert Weilguni; Harald Kling (WASSERWIRTSCHAFT, 2012)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Screening endoscopy and risk of colorectal cancer in United States men - Charles S. Fuchs; Edward L. Giovannucci; Graham A. Colditz; Anne M. Kavanagh (Cancer Causes & Control, 1998)